There Is No Rawlsian Theory of Corporate Governance. Issue 1 (24th February 2015) - Singer, Abraham
ABSTRACT: The major aim of this article is to show that John Rawls's theory of justice cannot be applied effectively to questions of business ethics and corporate governance. I begin with a reading of Rawls that emphasizes both the critical and pragmatic nature of his theory. In the second section I look more closely at the notion of society's "basic structure" and its place within Rawls's theory. In the third section, I argue that "the corporation" cannot be understood as part of this basic structure and is not, therefore, a subject of justice for Rawls or his interpreters. Finally, I show that Rawls's inability to speak to the corporation is a weakness, regardless of one's particular view on the corporation. I conclude by considering what Rawls's theory helps us to understand about the problems involved in integrating corporate governance, business ethics, and political philosophy.